Functionalized textile microplastics: A closer look at the issues, strategy, and legislation on the microplastic reduction (Kuwait Journal of Science)
The problem of microplastic pollution has become more prominent as a worldwide concern. This article provides a thorough analysis of the various routes by which microplastics originating from textiles are released into the environment, encompassing soil, air, and water. This review paper provides a succinct summary of the current use of hazardous and toxic substances (such as per polyfluoroalkyl substances (PFAS), chlorine, bromine, phosphorous, halogen-based chemicals, and various formaldehyde compounds), as well as dyes (which frequently contain heavy metals like lead, arsenic, chromium, nickel, copper, cadmium, mercury, and zinc), and nanomaterials in the textile production process. Additionally, the paper examines the role of the United Nations Environment Assembly (UNEA) and the development of its resolutions on marine plastic pollution to tackle the issue of reducing microplastics in textiles. Though there is a dearth of comprehensive coverage on this topic, this paper provides an overview of the legislative and regulatory measures implemented by different countries in response to the issue of microplastic generation and focuses on textile origin. © 2025 The Author